CIRCADIAN BLOOD PRESSURE MONITORING AND ARTERIAL TONE FEATURES IN YOUNG PEOPLE WITH HIGH NORMAL BLOOD PRESSURE - E. L. Snigur; M. E. Statsenko; E. I. Volchansky; A. N. Zhidkikh (Российский кардиологический журнал)
In total, 40 patients, aged 19–28 years, with high normal blood pressure, HNBP (classification by the Society of Cardiology of the Russian Federation, 2008) were examined. The analysed parameters of 24-hour blood pressure monitoring (BPM) included mean 24-hour BP levels, time index, 24-hour index, amplitude and rate of the morning BP surge, BP variability, and arteriolar tone. Over 50% of the young people with HNBP demonstrated an increase in vascular tone, time index, BP variability, morning surge rate, and the percentage of non-dippers. In participants with normal or decreased arteriolar tone, the values of time index, BP variability, morning surge rate and mean 24 BP were significantly lower. Therefore, high BP pathogenesis could be different among young people with HNBP: in those with high vascular tone, it is related to vasoconstriction, while in those with normal or reduced vascular tone, it might be due to disturbed autonomic regulation and autonomic vascular dystonia.